Rogerzetes lacouturieri n. gen., n. sp., (Acari: Oribatida: Eremaeozetidae) from Madagascar - Fernández, Néstor Alfredo (2011)
Rogerzetes lacouturieri n. gen., n. sp., collected from Manankaza Forest Station, Ambohitantely, Tananarive, Madagascar, is described and illustrated based on adult specimens. The new genus is distinguishable by the following combination of character states: body flattened; posterior part of lamellae fused, forming plate-like structure with rounded margin partially covering the bothridia; central posterior part plate-like, with tongue-like expansion surpassing dorsosejugal furrow; end of longitudinal fissure round–ovoid; large apical lamellae; naso and prodorsal sensory structures present; tube between le and sensory structure; in absent; prehumeral tecta prominent, partially covering the bothridia; 10 pairs of notogastral setae; anal plate ending in long spine; legs heterotridactylous. The new species is characterized by the following combination of characteristics cuticular microsculpture of foveate pattern; prodorsum with internal well-developed sensory structure; anterior part of notogaster, between dorsosejugal furrow and lenticulus, flat, semi-circular area, and at lower level than surrounding notogaster; prehumeral tecta ear-like; notogastral setae short and rod-like; epimeral setation (3-1-1-2). Eremaeozetes betschi, Fernandez and Cleva, 2009, is transferred to the new genus.